Rapid Treatment of Leukostasis in Leukemic Mantle Cell Lymphoma Using Therapeutic Leukapheresis: A Case Report. (16th August 2011) - Nguyen, Xuan Duc; La Rosée, Paul; Nebe, Thomas; Klüter, Harald; Buchheidt, Dieter
Abstract : We describe a case of severe leukocytosis caused by leukemic mantle cell lymphoma (MCL), complicated by leukostasis with myocardial infarction in which leukapheresis was used in the initial management. A 73-year-old male presented to the emergency department because of fatigue and thoracic pain. Blood count revealed 630 × 10 9 /L WBC (white blood cells). The electrocardiogram showed ST-elevation with an increase of troponin and creatinine kinase. The diagnosis was ST-elevation myocardial infarction (STEMI) induced and complicated by leukostasis. Immunophenotyping, morphology, cytogenetic and fluorescence- in-situ -hybridization analysis revealed the diagnosis of a blastoid variant of MCL. To remove leukocytes rapidly, leukapheresis was performed in the intensive care unit. Based on the differential blood count with 95% blasts, which were assigned to the lymphocyte population by the automatic hematology analyzer, leukapheresis procedures were then performed with the mononuclear cell standard program on the Spectra cell separator. The patient was treated with daily leukapheresis for 3 days. The WBC count decreased to 174 × 10 9 /L after the third leukapheresis, with a 72% reduction. After the second apheresis, treatment with vincristine, cyclophosphamide, and prednisolone was started. The patient fully recovered in the further course of the treatment. To the best of our knowledge, this is the first report on blastoid MCL with leukostasis associated with a STEMI that was successfully treated by leukapheresis. Effective harvest of circulating lymphoma cells by leukapheresis requires adaptation of instrument settings based on the results of the differential blood count prior to apheresis.